Transgressive and negotiated White racial knowledge. Issue 8 (13th September 2016) - Crowley, Ryan M.
Abstract: This critical case study investigated the experiences of six White preservice teachers as they learned about race and racism during the first semester of an urban-focused teacher preparation program. The author identified two broad themes of transgressive White racial knowledge and negotiated White racial knowledge to capture the participants' engagement with the topic of race. By detailing the complexities of the racial knowledge of a group of race-conscious White teachers, the project helps to de-homogenize conceptualizations of White teachers' racial identities. The transgressive knowledge displayed by the participants largely occurred in their intellectual understandings of issues related to urban education. When the participants discussed their antiracist practice and their own complicity in racism, their negotiations with critical understandings of race emerged. These findings suggest that educators working with race-conscious White teachers should emphasize the messiness inherent in enacting an antiracist practice and think differently about the subtle distancing strategies White teachers often deploy to release themselves from complicity in racism.